WORKING CAPITAL EFECTIVENESS PT GARUDAFOOD PUTRA PUTRI JAYA Tbk - Didi Rahmat; Fazira Wulanda (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2021)
This study aims to determine the efficiency of the allocation policy and sources of working capital at PT. Garudafood Putra Putri Jaya Tbk. The variable used is working capital with indicators of Working Capital Turnover, Working Capital Needs, and Working Capital Sources. The research period is 2017 to 2020. The data analysis uses quantitative descriptive and is then translated into graphic and narrative trends. From the data analysis, it is known that working capital turnover has been effective in creating a positive profit trend. Meanwhile, the working capital requirements during this period have been well met. Sources of working capital have basically used sources that can effectively support needs, except for low receivables turnover, so there are a lot of funds that should be used as sources but cannot be used.